Channel preferences: Unveiling omnichannel behavior in sports and leisure product purchases - Nagy Akos; Kemeny Ildiko; Szucs Krisztian (Management şi Marketing)
Current customer segmentations in omnichannel retail are based on channel usage and tend to be rather descriptive. In comparison, this research focuses on the role of “need for touch” (NFT) and channel preferences (attractiveness, appropriateness, satisfactoriness) introduced as antecedents to channel choice. The aim of this research was to develop a predictive model of omnichannel purchase behaviour and use its results to identify customer segments in the so far under-researched sports and leisure category, where the key decision factor of NFT seems to dominate when considering information and purchase options. We have examined its role and incorporated it as an exogenous variable and channel preferences as mediating variables in a SEM model to predict omnichannel purchase behaviour. Using the latent scores of channel preferences, we performed a cluster analysis and introduced various segments. In the proposed structural model preferences towards the information channel and the purchase channel serve as key mediators. Webrooming behaviour is negatively related to offline search channel preference, but showrooming is positively related to it. Meanwhile, webrooming behaviour is positively related to offline shopping channel preference, but showrooming is negatively related to it. Competitive mediation results indicate cross-channel synergies and complementary mediation results point out lock-in effects. Six customer segments were identified, and we found significant differences in their shopping behaviour. Lock-in effect arises in the case of online information enthusiasts and online shopping enthusiasts. While in the case of the webrooming-oriented cluster, offline shopping was more appropriate and satisfactory, and positive cross-channel synergies appeared to be prevalent.